Unveiling TikTok's Impact on Youth Communication: Mengungkap Dampak TikTok pada Komunikasi Anak Muda - Sabila, Amelia Hidayatus; Hadi, Bintang Khalishah; Gimnastiar, Ahmad; Abadi , Totok Wahyu (House of Wisdom: Journal on Library and Information Sciences, 2024)
This study aims to investigate the impact of TikTok as a web-based entertainment platform on young people's communication development. The research uses a bibliometric analysis approach, drawing from scientific articles and journals indexed by Crossref and sourced via Google Scholar, covering the years 2013-2023. Data collection involved using the Publish or Perish (PoP) program to gather bibliographic information, which was then validated and manually inputted using Mendeley Desktop. Analysis was performed with VOSviewer to create mapping visualizations. Results showed the highest Crossref publication index in 2020 with 96 publications. Keyword analysis identified five clusters, with Cluster 1 containing 102 items in red. The term "Children" appeared most frequently, with 1134 instances, highlighting the significant focus on early childhood communication development influenced by TikTok. The author collaboration analysis revealed that the most connected author had two links. These findings suggest that TikTok has a notable impact on early communication development, as evidenced by the concentrated research efforts and collaborative networks in this field. Highlights: TikTok's Influence: TikTok significantly impacts early childhood communication development. Publication Trends: Highest research publication peak in 2020 with 96 studies. Keyword Clusters: Five keyword clusters identified, highlighting key research areas. Keywords: TikTok, communication development, young people, bibliometric analysis, VOSviewer